THE STATE OF NURSES’ HEALTH ACCORDING TO A SOCIOLOGICAL SURVEY - Смагулов, Нурлан Кемельбекович; Агеев, Дмитрий Владимирович (Medicine in Kuzbass, 2023)
The assessment of the nurses’ health status is complicated by the fact that many of them do not seek official medical and preventive care, resorting to the help of colleagues and self-medication.The purpose – to determine the main factors affecting the health indicators and morbidity of nurses.Materials and methods. The study involved nurses of Karaganda hospitals aged from 19 to 59 years (72 persons). The subjects were divided into 3 age categories: under 30 years old, 30-45 years old and over 45 years old. The sociological survey was conducted using questionnaires for assessing medical and preventive activity and self-assessment of one's own health. Statistical processing was carried out using Excel 2019 and Statistica 10.0 programs.Results. According to the results of the survey, diseases of the cardiovascular system, respiratory tract, digestive system, musculoskeletal system, hormonal disorders and metabolic disorders took the first place in the structure of diseases (in descending order). The respondents rated the working conditions as good and satisfactory, the positive assessment decreased with age. Specifically, according to the factors of working conditions, respondents were not satisfied by temperature, drafts, illumination and noise at the workplace (in descending order).The leading negative production factor is not physical inactivity, but nervous and emotional tension. The work of nurses requires physical and mental effort, mental balance. In the process of work, nurses are dominated by a state of emotional tension. Nurses need the following psychological qualities: self-confidence and the ability not to get lost in difficult situations. Low medical activity, poor-quality attitude to their own health was noted in nurses.Conclusion. The results of a questionnaire survey of nurses in relation to cases of past illnesses allowed obtaining an objective assessment of nurses’ morbidity due to information about diseases with which they did not seek medical help.
Keywords: nurses; questioning; morbidity; working conditions; medical activity